Effects of Polar Steroids from the Starfish Patiria (=Asterina) pectinifera in Combination with X-Ray Radiation on Colony Formation and Apoptosis Induction of Human Colorectal Carcinoma Cells - Olesya S. Malyarenko; Timofey V. Malyarenko; Alla A. Kicha; Natalia V. Ivanchina; Svetlana P. Ermakova (Molecules, 2019)
Despite significant advances in the understanding, prevention, and treatment of cancer, the disease continues to affect millions of people worldwide. Chemoradiation therapy is a rational approach that has already proven beneficial for several malignancies. However, the existence of toxicity to normal tissue is a serious limitation of this treatment modality. The aim of the present study is to investigate the ability of polar steroids from starfish Patiria (=Asterina) pectinifera to enhance the efficacy of radiation therapy in colorectal carcinoma cells. The cytotoxic activity of polar steroids and X-ray radiation against DLD-1, HCT 116, and HT-29 cells was determined by an MTS assay. The effect of compounds, X-ray, and their combination on colony formation was studied using the soft agar method. The molecular mechanism of the radiosensitizing activity of asterosaponin P1 was elucidated by western blotting and the DNA comet assay. Polar steroids inhibited colony formation in the tested cells, and to a greater extent in HT-29 cells. Asterosaponin P1 enhanced the efficacy of radiation and, as a result, reduced the number and size of the colonies of colorectal cancer cells. The radiosensitizing activity of asterosaponin P1 was realized by apoptosis induction through the regulation of anti- and pro-apoptotic protein expression followed by caspase activation and DNA degradation.